Interactive communication with clustering collaboration for wireless powered communication networks - Lina Yuan; Huajun Chen; Jing Gong (International Journal of Distributed Sensor Networks)
In this article, we propose a novel wireless powered communication network, which is composed of two multiple antennas hybrid access points and a series of distributed wireless devices. The two hybrid access points transmit downlink wireless energy to the wireless devices and receive uplink wireless messages from the wireless devices; meanwhile, the information of wireless devices nearer to their corresponding hybrid access point should be transmitted to the faraway hybrid access point. To improve the throughput performance of some wireless devices away from their corresponding hybrid access point, we propose a clustering-collaboration interactive communication protocol with multiple antennas by Time Division Multiple Access, where two of the distributed wireless devices are selected as cluster heads to help relay information of other cluster members, which can efficiently improve some faraway wireless devices’ throughput performance. However, its performance is also constrained by cluster heads’ high-energy consumption. To solve this energy imbalance problem, multi-antenna energy beamforming technology is exploited for the hybrid access points, which distributes more transmission power to the cluster heads to balance all the wireless devices’ energy consumption. In particular, we obtain the proposed system’s throughput performance through the multi-antenna cluster-based collaboration, and verify through simulations that this scheme can effectively enhance user unfairness and improve the throughput performance.